Plasma-laser assisted synthesis of nanoparticles for antibacterial coatings - Jurov, A. (2017)
The “green synthesis” of colloidal nanoparticles and their application for the antibacterial coatings is based on the plasma-laser assisted ablation in liquids. Nanoparticles are synthesized through the process of laser ablation of target in water, which enables additional advantages in comparison with the other standard wet chemical synthesis, such as simplicity and complete utilization of materials. Furthermore, these nanoparticles are used and tested for antibacterial coatings on polymers, where they are grafted or imbedded through atmospheric pressure plasma assisted processes. The advantages of different coatings made from those nanoparticles are presented as well.